Challenges In Producing Porous Starch: A Comparative Insight Between Sago And Corn Starch - Kai Xuan, Camilias OO (Universiti Sains Malaysia, 2020)
Native starch has limited industrial usages due to its unstable properties. With the industry demand for consistency of raw materials, there is a growing interest in using modified starch as food ingredients instead of native starch. In recent years, porous starch has gained its acceptance in food industry owing to its adsorption and encapsulation ability. Porous starch can be obtained from different botanical sources, however, the pore-forming efficiency will be different due to the effect of starch types with varied surface characteristics, granule size, internal structure, amyloseamylopectin ratio or the presence of compound granule. Among the starches, corn starch is the most preferred type for porous starch production due to the high susceptibility to pore formation and it has been commercialized so far, like StarrierR® and Cargill. Sago starch, an example of resistant-type starch, is less likely to be used in producing porous starch although it is widely available in Malaysia, owing to the low pore-forming efficiency. Therefore, this review enlightens the challenges in producing porous starch which have rarely been discussed among researchers, mainly focused on the effect of starch types and enzyme types. A comparative insight is also presented by investigating the effects of similar treatments (freeze thawing, ethanol wash, heat moisture treatment, ultrasonic, enzyme hydrolysis) on the development porous structure in resistant-type and susceptible-type starches, using sago and corn starch as examples. SEM micrographs demonstrated the different extent of pore formation in sago and corn starch although similar treatments were applied.